Enhancing English Language Learning in Higher Education through Instagram: A Design and Development Approach - Syakur, Abd.; Padmadewi, Ni Nyoman; Adnyani, Ni Luh Putu Sri; Prasetya, Rizki; Prawoco, Fajar Sandi (Universitas Negeri Padang, 2023)
This study investigates the utilization of Instagram as a tool for enhancing English language learning among higher education students. Amidst the growing influence of social media on student lifestyles, the research aimed to harness Instagram's potential for educational purposes, particularly in language acquisition. Employing a Design and Development (D&D) approach with the four-dimensional (4D) model - Define, Design, Development, and Dissemination - the study focused on creating and implementing English learning materials tailored for the Instagram platform. The research methodology included the use of a questionnaire to assess the effectiveness of the instructional materials. These materials were validated by a panel consisting of two media experts, two language experts, and two material experts, ensuring content validity. The study involved a purposively selected sample of 30 students, emphasizing first-semester English majors who were active Instagram users. This approach facilitated an evaluation of the reliability and validity of the instructional materials and the research instrument. Key findings indicated that Instagram as a learning platform significantly boosted student engagement and interaction in English language learning. The study revealed the importance of social media, particularly Instagram, in fostering a more interactive and engaging learning environment. However, the research faced limitations due to its reliance on self-reported data and its focus on a specific student demographic. The study recommends future research to expand beyond first-semester English majors and explore various social media content types for effective educational outcomes. Longitudinal studies and qualitative research methods are suggested to gain deeper insights into student interactions with social media in educational contexts. This research underscores the potential of integrating social media platforms like Instagram into educational curricula, tailored to the digital habits and preferences of contemporary students.